NGAL as an Early Predictive Marker of Diabetic Nephropathy in Children and Young Adults with Type 1 Diabetes Mellitus. (23rd May 2017) - Papadopoulou-Marketou, Nektaria; Margeli, Alexandra; Papassotiriou, Ioannis; Chrousos, George P.; Kanaka-Gantenbein, Christina; Wahlberg, Jeanette
Abstract : Aims . Type 1 diabetes (T1D) is often associated with early microvascular complications. Previous studies demonstrated that increased systolic (SAP) and diastolic arterial blood pressures (DAP) are linked to microvascular morbidity in T1D. The aim of the study was to investigate the predictive role of neutrophil gelatinase-associated lipocalin (NGAL) in unravelling early cardio-renal dysfunction in T1D. Methods . Two T1D patient groups participating in two-centre prospective cohorts were studied. Group A consisted of 57 participants aged 13.9 years (SD: 3.1) and group B consisted of 59 patients aged 28.0 years (SD: 4.4). Forty-nine healthy children [age: 10.5 years (SD: 6.6)] and 18 healthy adults [age 27.7 years (SD: 4.2)] served as controls. Serum concentrations of NGAL (ELISA) were determined, and SAP and DAP were examined (SAP and DAP also expressed as z -scores in the younger group). Results . NGAL correlated positively with SAP in both patient groups (P = 0.020 and P = 0.031, resp.) and SAP z -score (P = 0.009 ) (group A) and negatively with eGFR in both groups (P < 0.001 and P < 0.001, resp.). Conclusions . NGAL may be proposed as a biomarker of early renal dysfunction even in nonalbuminuric T1D patients, since it was strongly associated with renal function decline and increasing systolic arterial pressure even at prehypertensive range in people with T1D, in a broad age range.